Antifouling and anti-fingerprint glass coating and preparation method thereof

By using perfluoroalkyl ethylene and fluoromodified acrylate to form perfluoroalkyl oligomers and reacting with siloxanes to form perfluoroalkyl siloxanes, the problems of complex preparation and poor adhesion in the prior art are solved, and the coating effect of high adhesion, wear resistance, corrosion resistance and oleophobic and hydrophobic coating effect is achieved.

CN119899589AInactive Publication Date: 2025-04-29CHANGSHA DAIHUA TECH CO LTD
View PDF 17 Cites 0 Cited by

Patent Information

Application Number
CN202411869575.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-29
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the preparation process of glass coatings is complicated and not suitable for large-scale production. The coating functions are single, with poor adhesion and easy to fall off.

Method used

Perfluoroalkyl ethylene and fluoromodified acrylate are used as raw materials to form perfluoroalkyl oligomers with molecular weight of 4000-8000 by addition and react with siloxane to form perfluoroalkyl siloxane, and then sprayed onto microcrystalline glass by evaporation or dilution to form a stable fluorine-containing coating.

Benefits of technology

The coating preparation process is simplified and suitable for large-scale production. The coating has strong adhesion, wear resistance, corrosion resistance, is not easy to fall off, and has excellent oleophobic and hydrophobic effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899589A_ABST
    Figure CN119899589A_ABST
Patent Text Reader

Abstract

The preparation method comprises the following steps: uniformly mixing and stirring 40-60 parts by mass of perfluoroalkyl ethylene and 20-40 parts by mass of fluorine-modified acrylate, heating and stirring to 80-100 DEG C, carrying out a constant-temperature reaction for 8-10 h, removing impurities to obtain a perfluoroalkyl oligomer with the molecular weight of 4000-8000, adding the perfluoroalkyl oligomer into a reaction kettle, carrying out a reaction at the temperature of 80-100 DEG C, and carrying out a reaction at the temperature of 80-100 DEG C for 8-10 h to obtain the anti-fouling and anti-fingerprint glass coating with the anti-fouling and anti-fingerprint functions. Adding 10-40 parts of siloxane, and reacting at 40-80 DEG C for 3-4 hours to obtain perfluoroalkyl siloxane; and diluting the perfluoroalkyl siloxane with a fluorocarbon-containing solvent to obtain the coating. The coating provided by the invention is simple in preparation method and can be produced on a large scale; the coating has the characteristics of hydrophobicity, oleophobicity, easiness in cleaning, fingerprint prevention and the like, is excellent in adhesive force, scratch-resistant and wear-resistant, can protect the glass surface for a long time, and is suitable for common glass and microcrystalline glass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of microcrystalline glass coatings, and more specifically, relates to an anti-fouling and anti-fingerprint glass coating and a preparation method thereof. Background Art

[0002] In recent years, the touch panelization of screens has been accelerating, represented by mobile phone displays. However, the glass surface that is frequently touched is easily contaminated by fingerprints, sweat, cosmetics, etc. Once contaminated, it is difficult to remove and affects its appearance and use. Due to the unique chemical stability, temperature resistance, low friction coefficient and low surface tension of the perfluoropolyether structure, it is widely used in anti-fingerprint coatings on the surface of touch screens.

[0003] The patent (application number 201710127998.5) discloses a super hydrophobic and oleophobic fluorocarbon coating, the components of which include epoxy resin, graphite fluoride, ammonium carbonate, polyoxyethylene ether, organic solvent a, curing agent and organic solvent b. The invention also discloses the preparation method and use method of the super hydrophobic and oleophobic fluorocarbon coating. The patent (application number 202121114054.2) discloses a new type of UV anti-fingerprint coating, wherein the substrate is provided with a waterproof coating, a high temperature coating, an anti-fingerprint coating, a silicone protective coating, etc.; the patent (application number 202110778093.0) discloses a preparation method and an anti-fingerprint agent of a perfluoropolyether siloxane compound, and the present invention efficiently prepares a series of perfluoropolyether siloxane compounds containing 1 to 4 siloxane groups by reacting acyl fluoride with alcohol or amine compounds containing different numbers of double bonds. The patent (application number 202120378797.4) discloses an anti-fingerprint touch screen panel, comprising a face frame and a touch screen, wherein the touch screen is covered with an anti-fingerprint coating. The patent (application number 202010382838.7) discloses a method for preparing an anti-fingerprint glass coating with a high friction coefficient. The preparation method of the coating used in the coating comprises the following steps: according to the mass parts, 20-25 parts of perfluoroalkyl olefin, 8-12 parts of vinyl methoxysilane, and 6-8 parts of hexamethyldisiloxane are mixed evenly, stirred, and then heated to 80℃-100℃, kept at a constant temperature for 10h-12h, and then heated to 110-120℃ with silicone oil for 4h-6h to obtain a perfluoropolyether alkylated oligomer with a molecular weight of 3000-4000; according to the mass parts, 15-25 parts of the above-obtained perfluoropolyether alkylated oligomer, 25-35 parts of nonafluoro-ethoxy-butane, and 45-55 parts of heptafluoro-ethoxydifluoromethyl-propane are stirred evenly to obtain the desired perfluoroalkylated coating. The coating is dispersed into a diluent fluorocarbon solvent at a ratio of 1:333 to obtain an anti-fingerprint spray coating.

[0004] The problems existing in the prior art are: 1. The coating preparation process is complicated and not suitable for large-scale production; 2. The coating has a single function, poor adhesion and is easy to fall off. Summary of the invention

[0005] In view of the defects existing in the prior art, the present invention provides an anti-fouling and anti-fingerprint glass coating and a preparation method thereof. Perfluoroalkyl ethylene and fluorine-modified acrylate are used as raw materials to form a perfluoroalkyl oligomer with a molecular weight of 4000-8000, which is then reacted with siloxane to obtain perfluoroalkyl siloxane, which is then sprayed onto microcrystalline glass by evaporation or dilution. After the surface of the microcrystalline glass is treated with plasma, active hydroxyl groups exist on the surface, which undergo dehydration condensation with the perfluoroalkyl siloxane to form a stable fluorine-containing coating.

[0006] The technical solution of the present invention to solve the above technical problems is as follows:

[0007] A method for preparing an anti-fouling and anti-fingerprint glass coating comprises the following steps:

[0008] According to the mass parts, 40-60 parts of perfluoroalkylethylene and 20-40 parts of fluorine-modified acrylate are mixed and stirred evenly, heated and stirred to 80°C-100°C, reacted at a constant temperature for 8-10h, and impurities were removed to obtain a perfluoroalkyl oligomer with a molecular weight of 4000-8000; 10-40 parts of siloxane were added, and the reaction was carried out at 40°C-80°C for 3-4h to obtain perfluoroalkyl siloxane; the perfluoroalkyl siloxane was diluted with a carbon-fluorine solvent to obtain a coating.

[0009] Reaction equation of the present invention is as follows:

[0010]

[0011] Wherein, n=2-10, PFAS represents perfluoroalkyl, R represents perfluoroalkyl oligomer, and M represents hydroxyl-containing surface such as inorganic metal and glass. In the present invention, perfluoroalkylethylene and fluorine-modified acrylate undergo addition polymerization to form perfluoroalkyl oligomer, which then reacts with siloxane to form perfluoroalkylsiloxane. Perfluoroalkylsiloxane can combine with hydroxyl groups on the surface of inorganic metal and glass to form a fluorine-containing coating with strong adhesion.

[0012] Furthermore, the carbon chain length of the perfluoroalkyl group in the perfluoroalkylethylene is C4 to C12, preferably one or more of 1H, 1H, 2H-perfluoro-1-undecene and heptadecafluoro-1-decene.

[0013] Furthermore, the fluorine-modified acrylate includes any one or more of perfluoroacrylate, hexafluorobutyl methacrylate, hexafluorobutyl acrylate, trifluoroethyl methacrylate, and heptafluorobutyl acrylate.

[0014] Furthermore, the impurities are removed by heating to 100°C-120°C and removing them by rotary distillation.

[0015] Furthermore, the siloxane includes any one or more of methoxysiloxane, ethoxysiloxane, hexamethyldisiloxane, decamethyltetrasiloxane, and cyclotrisiloxane.

[0016] Furthermore, the fluorine-containing carbon solvent is a mixture of hexafluoropropylene dimers or trimers.

[0017] Furthermore, the mass ratio of the perfluoroalkylsiloxane to the fluorine-containing carbon solvent is 0.1-0.5:99.5-99.9.

[0018] The invention also provides an anti-fouling and anti-fingerprint glass coating prepared by the method.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The invention uses perfluoroalkylethylene and fluorine-modified acrylate as raw materials to form a perfluoroalkyl oligomer with a molecular weight of 4000-8000, and then reacts with siloxane to obtain perfluoroalkyl siloxane. The preparation method is simple, has low requirements on equipment, and can be mass-produced.

[0021] The coating prepared by the preparation method of the present invention can be sprayed onto microcrystalline glass by evaporation or dilution, and can dehydrate and condense with the active hydroxyl groups on the surface of the microcrystalline glass to form a stable fluorine-containing coating with strong adhesion, wear resistance, corrosion resistance, not easy to fall off, and excellent oleophobic and hydrophobic effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The water contact angle test results of the coatings prepared in Example 1 and Comparative Example 1;

[0023] Among them, a, the initial water contact angle of Example 1; b, the initial water contact angle of Example 1 after being treated with steel wool 5000 times; c, the initial water contact angle of Comparative Example 1; d, the initial water contact angle of Comparative Example 1 after being treated with steel wool 5000 times. DETAILED DESCRIPTION

[0024] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. It should be noted that the reagents used in the present embodiment are all common commercial products.

[0026] Embodiment 1

[0027] Preparation of perfluoroalkylsiloxane coating:

[0028] Prepare a 100ml three-necked bottle device with temperature display and stirring function, add 9.92g of 1H,1H,2H-perfluoro-1-undecene and 4.72g of hexafluorobutyl acrylate, stir evenly, heat to 80℃-100℃, keep constant temperature for 8-10h, add to a double-layer glass kettle with stirring function, heat to 100℃-120℃ through silicone oil and purify to obtain a perfluoroalkylated oligomer with a molecular weight of 4000-8000. Add 1g of trimethoxysiloxane to 10.0g of perfluoroalkyl oligomer, stir evenly and heat to 40℃-80℃, keep constant temperature for 3-4h to obtain a perfluoroalkylsiloxane coating stock solution. Take 3g of perfluoroalkylsiloxane coating stock solution, add it to 1000g of fluorocarbon solvent, stir evenly, obtain a perfluoroalkylsiloxane coating, and set aside.

[0029] Processing of glass-ceramic materials:

[0030] Send the microcrystalline glass substrate into the ultrasonic cleaning equipment, clean it with cleaning solution for 10 minutes, and then rinse it with clean water for 5 minutes to remove the residual cleaning solution on the microcrystalline glass substrate layer; then, rinse it with pure water for 5 times, and finally take out the glass substrate after slowly pulling it with pure water and place it in the oven to dry for use.

[0031] Preparation of antifouling coating on glass-ceramic:

[0032] The cleaned and dried glass is bombarded with two groups of plasmas in turn, and two special spray guns with a caliber of 0.3 are selected to spray the anti-fingerprint coating on the surface of the glass substrate layer in parallel. The sprayed glass needs to be sent to the oven for preheating for 5 to 10 minutes, and the preheating temperature is set at 100°C: after the preheating is completed, it is sent to the curing furnace for heating and curing, and the furnace temperature of the curing furnace is set at 160°C, and the curing time is 20 minutes; after the glass leaves the curing furnace, it should be naturally cooled to room temperature, and the microcrystalline glass with the anti-fingerprint coating is obtained.

[0033] Embodiment 2

[0034] Preparation of perfluoroalkylsiloxane coating:

[0035] Prepare a 100ml three-necked bottle device with temperature display and stirring function, add 8.92g of 17fluoro-1-decene, 5.0g of hexafluorobutyl methacrylate, stir evenly, heat to 80℃-100℃, keep constant temperature for 8-10h, add to a double-layer glass kettle with stirring function, heat to 100℃-120℃ through silicone oil and purify to obtain a perfluoroalkylated oligomer with a molecular weight of 4000-8000. Add 1.2g of triethoxysiloxane to 10.0g of perfluoroalkyl oligomer, stir evenly and heat to 40℃-80℃, keep constant temperature for 3-4h to obtain a perfluoroalkylsiloxane coating stock solution. Take 3g of perfluoroalkylsiloxane coating stock solution, add it to 1000g of fluorocarbon solvent, stir evenly, obtain a perfluoroalkylsiloxane coating, and set aside.

[0036] Processing of glass-ceramic materials:

[0037] Send the microcrystalline glass substrate into the ultrasonic cleaning equipment, clean it with cleaning solution for 10 minutes, and then rinse it with clean water for 5 minutes to remove the residual cleaning solution on the glass substrate layer; then, rinse it with pure water for 5 times, and finally take out the glass substrate after slowly pulling it with pure water and place it in the oven to dry for use.

[0038] Preparation of antifouling coating on glass-ceramic:

[0039] The cleaned and dried microcrystalline glass is bombarded by two groups of plasmas on the surface of the microcrystalline glass in turn, and two special spray guns with a caliber of 0.3 are selected to spray the anti-fingerprint coating on the surface of the glass substrate layer in parallel. The sprayed glass needs to be sent to the oven for preheating for 5 to 10 minutes, and the preheating temperature is set at 100°C: after the preheating is completed, it is sent to the curing furnace for heating and curing, and the furnace temperature of the curing furnace is set at 160°C, and the curing time is 20 minutes; after the glass leaves the curing furnace, it should be naturally cooled to room temperature, and the microcrystalline glass with the anti-fingerprint coating is obtained.

[0040] Embodiment 3

[0041] Preparation of perfluoroalkylsiloxane coating:

[0042] Prepare a 100ml three-necked bottle device with temperature display and stirring function, add 9.92g of 1H,1H,2H-perfluoro-1-undecene and 4.72g of hexafluorobutyl acrylate, stir evenly, heat to 80℃-100℃, keep constant temperature for 8-10h, add to a double-layer glass kettle with stirring function, heat to 100℃-120℃ through silicone oil and purify to obtain a perfluoroalkylated oligomer with a molecular weight of 4000-8000. Add 1g of trimethoxysiloxane to 10.0g of perfluoroalkyl oligomer, stir evenly and heat to 40℃-80℃, keep constant temperature for 3-4h to obtain a perfluoroalkylsiloxane coating stock solution. Take 5g of perfluoroalkylsiloxane coating stock solution, add it to 1000g of fluorocarbon solvent, stir evenly, obtain a perfluoroalkylsiloxane coating, and set aside.

[0043] Processing of glass-ceramic materials:

[0044] Send the microcrystalline glass substrate into the ultrasonic cleaning equipment, clean it with cleaning solution for 10 minutes, and then rinse it with clean water for 5 minutes to remove the residual cleaning solution on the glass substrate layer; then, rinse it with pure water for 5 times, and finally take out the glass substrate after slowly pulling it with pure water and place it in the oven to dry for use.

[0045] Preparation of antifouling coating on glass-ceramic:

[0046] The cleaned and dried microcrystalline glass is bombarded with two groups of plasmas in turn, and two special spray guns with a caliber of 0.3 are selected to spray the anti-fingerprint coating on the surface of the glass substrate layer in parallel. The sprayed glass needs to be sent to the oven for preheating for 5 to 10 minutes, and the preheating temperature is set at 100°C: after the preheating is completed, it is sent to the curing furnace for heating and curing, and the furnace temperature of the curing furnace is set at 160°C, and the curing time is 20 minutes; after the glass leaves the curing furnace, it should be naturally cooled to room temperature, and the microcrystalline glass with the anti-fingerprint coating is obtained.

[0047] Embodiment 4

[0048] Preparation of perfluoroalkylsiloxane coating:

[0049] Prepare a 100ml three-necked bottle device with temperature display and stirring function, add 9.92g of 1H,1H,2H-perfluoro-1-undecene and 4.72g of hexafluorobutyl acrylate, stir evenly, heat to 80℃-100℃, keep constant temperature for 8-10h, add to a double-layer glass kettle with stirring function, heat to 100℃-120℃ through silicone oil and purify to obtain a perfluoroalkylated oligomer with a molecular weight of 4000-8000. Add 1g of trimethoxysiloxane to 10.0g of perfluoroalkyl oligomer, stir evenly and heat to 40℃-80℃, keep constant temperature for 3-4h to obtain a perfluoroalkylsiloxane coating stock solution. Take 3g of perfluoroalkylsiloxane coating stock solution, drip it on a steel wool carrier, and obtain a perfluoroalkylsiloxane target pellet for standby use.

[0050] Processing of glass-ceramic materials:

[0051] Send the microcrystalline glass substrate into the ultrasonic cleaning equipment, clean it with cleaning solution for 10 minutes, and then rinse it with clean water for 5 minutes to remove the residual cleaning solution on the glass substrate layer; then, rinse it with pure water for 5 times, and finally take out the glass substrate after slowly pulling it with pure water and place it in the oven to dry for use.

[0052] Preparation of antifouling coating on glass-ceramic:

[0053] Put the cleaned and dried glass and target pellets into the vacuum coating equipment, and evacuate the vacuum to 1.0*10-3Pa to preheat the film material. Start the electron gun and increase the current to 100mA for pre-melting. Then, when the current is increased to 300mA, the film material evaporates and accumulates on the surface of the substrate. When the thickness reaches 20nm, stop evaporation. When the vacuum reaches 8.0*10-4Pa, start the molybdenum boat to heat the target pellet. The preheating current is 50mA for 1 minute. After increasing the current to 95mA for 5 minutes, the coating is completely evaporated to the surface of the substrate. After the above is completed, turn off the vacuum, open the vent valve and take it out when the air pressure is balanced, and the microcrystalline glass with the above anti-fingerprint coating is obtained.

[0054] Embodiment 5

[0055] Preparation of perfluoroalkylsiloxane coating:

[0056] Prepare a 100ml three-necked bottle device with temperature display and stirring function, add 9.92g of 1H,1H,2H-perfluoro-1-undecene and 4.72g of hexafluorobutyl acrylate, stir evenly, heat to 80℃-100℃, keep constant temperature for 8-10h, add to a double-layer glass kettle with stirring function, heat to 100℃-120℃ through silicone oil and purify to obtain a perfluoroalkylated oligomer with a molecular weight of 4000-8000. Add 1g of trimethoxysiloxane to 10.0g of perfluoroalkyl oligomer, stir evenly and heat to 40℃-80℃, keep constant temperature for 3-4h to obtain a perfluoroalkylsiloxane coating stock solution. Take 3g of perfluoroalkylsiloxane coating stock solution, add it to 1000g of fluorocarbon solvent, stir evenly, obtain a perfluoroalkylsiloxane coating, and set aside.

[0057] AGC glass material processing:

[0058] Send the AGC glass substrate into an ultrasonic cleaning device, clean it with cleaning solution for 10 minutes, then rinse it with clean water for 5 minutes to remove the residual cleaning solution on the AGC glass substrate layer; then, rinse it with pure water for 5 times, and finally take out the AGC glass substrate after slowly pulling it with pure water and place it in an oven to dry for later use.

[0059] Preparation of AGC glass antifouling coating:

[0060] The cleaned and dried glass is bombarded with two groups of plasma on the AGC glass surface in turn, and two special spray guns with a caliber of 0.3 are selected to spray the anti-fingerprint coating on the surface of the AGC glass substrate layer in parallel. The sprayed AGC glass needs to be sent to the oven for preheating for 5 to 10 minutes, and the preheating temperature is set at 100°C: after the preheating is completed, it is sent to the curing furnace for heating and curing, and the furnace temperature of the curing furnace is set at 160°C, and the curing time is 20 minutes; after the glass leaves the curing furnace, it should be naturally cooled to room temperature, and the AGC glass with the anti-fingerprint coating is obtained.

[0061] Comparative Example 1

[0062] Preparation of perfluoropolyether siloxane coating:

[0063] Take 3 g of commercially available perfluoropolyether siloxane stock solution, add it into 1000 g of fluorocarbon solvent, stir evenly, and obtain perfluoropolyether siloxane coating for later use.

[0064] Processing of glass-ceramic materials:

[0065] Send the microcrystalline glass substrate into the ultrasonic cleaning equipment, clean it with cleaning solution for 10 minutes, and then rinse it with clean water for 5 minutes to remove the residual cleaning solution on the glass substrate layer; then, rinse it with pure water for 5 times, and finally take out the glass substrate after slowly pulling it with pure water and place it in the oven to dry for use.

[0066] Preparation of antifouling coating on glass-ceramic:

[0067] The cleaned and dried microcrystalline glass is bombarded with two groups of plasmas in turn, and two special spray guns with a caliber of 0.3 are selected to spray the anti-fingerprint coating on the surface of the glass substrate layer in parallel. The sprayed glass needs to be sent to the oven for preheating for 5 to 10 minutes, and the preheating temperature is set at 100°C: after the preheating is completed, it is sent to the curing furnace for heating and curing, and the furnace temperature of the curing furnace is set at 160°C, and the curing time is 20 minutes; after the glass leaves the curing furnace, it should be naturally cooled to room temperature, and the microcrystalline glass with the anti-fingerprint coating is obtained.

[0068] Comparative Example 2

[0069] Preparation of perfluoroalkylsiloxane coating:

[0070] Prepare a 100ml three-necked bottle device with temperature display and stirring function, add 9.92g of 1H,1H,2H-perfluoro-1-undecene and 4.72g of hexafluorobutyl acrylate, stir evenly, heat to 80℃-100℃, keep constant temperature for 8-10h, add to a double-layer glass kettle with stirring function, heat to 80℃-100℃ through silicone oil and condense to obtain a perfluoroalkylated oligomer with a molecular weight of less than 4000. Add 1g of trimethoxysiloxane to 10.0g of perfluoroalkyl oligomer, stir evenly and heat to 40℃-80℃, keep constant temperature for 3-4h to obtain a perfluoroalkylsiloxane coating stock solution. Take 3g of perfluoroalkylsiloxane coating stock solution, add it to 1000g of fluorocarbon solvent, stir evenly, and obtain a perfluoroalkylsiloxane coating for standby use.

[0071] Processing of glass-ceramic materials:

[0072] Send the microcrystalline glass substrate into the ultrasonic cleaning equipment, clean it with cleaning solution for 10 minutes, and then rinse it with clean water for 5 minutes to remove the residual cleaning solution on the glass substrate layer; then, rinse it with pure water for 5 times, and finally take out the glass substrate after slowly pulling it with pure water and place it in the oven to dry for use.

[0073] Preparation of antifouling coating on glass-ceramic:

[0074] The cleaned and dried microcrystalline glass is bombarded with two groups of plasmas in turn, and two special spray guns with a caliber of 0.3 are selected to spray the anti-fingerprint coating on the surface of the glass substrate layer in parallel. The sprayed glass needs to be sent to the oven for preheating for 5 to 10 minutes, and the preheating temperature is set at 100°C: after the preheating is completed, it is sent to the curing furnace for heating and curing, and the furnace temperature of the curing furnace is set at 160°C, and the curing time is 20 minutes; after the glass leaves the curing furnace, it should be naturally cooled to room temperature, and the microcrystalline glass with the anti-fingerprint coating is obtained.

[0075] Comparative Example 3

[0076] Preparation of fluorinated alkylsiloxane coatings:

[0077] Prepare a 100ml three-necked flask device with temperature display and stirring function, add 9.92g of 1H,1H,2H-perfluoro-1-undecene and 2g of methyl methacrylate, stir evenly, heat to 80℃-100℃, keep constant temperature for 8-10H, add to a double-layer glass kettle with stirring function, heat to 100℃-120℃ through silicone oil and purify to obtain a fluorinated alkylated oligomer with a molecular weight of 4000-8000. Add 1g of trimethoxysiloxane to 10.0g of fluorinated alkyl oligomer, stir evenly and heat to 40℃-80℃, keep constant temperature for 3-4h to obtain a fluorinated alkyl siloxane coating stock solution. Take 3g of fluorinated alkyl siloxane coating stock solution, add it to 1000g of fluorocarbon solvent, stir evenly, obtain a fluorinated alkyl siloxane coating, and set aside.

[0078] Processing of glass-ceramic materials:

[0079] Send the microcrystalline glass substrate into the ultrasonic cleaning equipment, clean it with cleaning solution for 10 minutes, and then rinse it with clean water for 5 minutes to remove the residual cleaning solution on the glass substrate layer; then, rinse it with pure water for 5 times, and finally take out the glass substrate after slowly pulling it with pure water and place it in the oven to dry for use.

[0080] Preparation of antifouling coating on glass-ceramic:

[0081] The cleaned and dried microcrystalline glass is bombarded with two groups of plasmas in turn, and two special spray guns with a caliber of 0.3 are selected to spray the anti-fingerprint coating on the surface of the glass substrate layer in parallel. The sprayed glass needs to be sent to the oven for preheating for 5 to 10 minutes, and the preheating temperature is set at 100°C: after the preheating is completed, it is sent to the curing furnace for heating and curing, and the furnace temperature of the curing furnace is set at 160°C, and the curing time is 20 minutes; after the glass leaves the curing furnace, it should be naturally cooled to room temperature, and the microcrystalline glass with the anti-fingerprint coating is obtained.

[0082] Performance testing

[0083] Test method:

[0084] The surface phenomenon is that the coated glass of Examples 1, 2, 3, 4, 5 and Comparative Examples 1, 2, 3 are taken out for comparison, and the surface condition of the glass and the state of the film layer are observed.

[0085] Water drop angle test: The coated glass of Examples 1, 2, 3, 4, 5 and Comparative Examples 1, 2, 3 is placed under a water drop angle tester for water drop angle test, the equipment model is SDC-200S.

[0086] Friction coefficient test: The coated glasses of Examples 1, 2, 3, 4, and 5 and Comparative Examples 1, 2, and 3 are placed in a friction coefficient tester, and the equipment model is MXD-02.

[0087] Friction resistance test: put the coated glass of Examples 1, 2, 3, 4, 5 and Comparative Examples 1, 2, 3 under the friction resistance tester for friction resistance test, using MB006004 model, 0.6cm*15cm specification rubber, load 1KG, friction speed 40 times / minute, stroke 40mm for rubber friction resistance test. Use 0000# steel wool, grinding head 1cm*1cm, friction speed 40 times / minute, stroke 40mm, load 1KG, steel wool friction resistance test. Equipment models HD-R837 and model339.

[0088] Alkali sweat resistance test: take a dust-free cloth, soak it in the prepared artificial sweat, and then take it out, making sure that sweat cannot drip directly on the dust-free cloth; use the dust-free cloth soaked in sweat to gently wipe the glass surface of Examples 1, 2, 3, 4, and 5, and Comparative Examples 1, 2, and 3 that have been coated back and forth for 2 minutes, with a wiping force of about 3-6N; place it at room temperature for 2 hours, and visually inspect the appearance

[0089] Salt spray resistance test: the coated glass of Examples 1, 2, 3, 4, 5 and Comparative Examples 1, 2 and 3 is placed in a salt spray tester for salt spray resistance test, the temperature is set at 35℃±2℃, the pH value is 6.5-7.2, 5%±1% of the salt spray box, and the NaCl solution is sprayed continuously for 48 hours. The equipment model is AP-YW-60. After the test, the surface treatment layer is removed from the test box and the appearance of the sample is checked; then it is gently rinsed with warm water not higher than 38℃, and wiped clean with a dust-free cloth, and the appearance of the sample is checked after being placed at room temperature for 2 hours.

[0090] For the thermal shock resistance test, the coated glasses of Examples 1, 2, 3, 4, 5 and Comparative Examples 1, 2 and 3 are placed in a three-chamber thermal shock test chamber for thermal shock resistance test. The equipment model is 3AP-CJ-27A. The coated glasses of Examples 1, 2, 3, 4, 5 and Comparative Examples 1, 2 and 3 are placed in the thermal shock resistance test chamber. They are first kept at a low temperature of -40°C ± 2°C for 1 hour. The temperature is switched to a high temperature of 70°C ± 2°C within 5 minutes and kept for 1 hour. The above is one sequence. After 24 cycles in total, the samples are taken out to inspect the appearance.

[0091] The test data is shown in Table 1.

[0092] Table 1

[0093]

[0094]

[0095] As shown in Table 1, compared to commercially available perfluoropolyether siloxane (Comparative Example 1), the coatings prepared by Examples 1 to 4 of the present invention are used for the surface of microcrystalline glass, and good adhesion, hydrophobic and oleophobic properties and corrosion resistance can be obtained, and good resistance to cold and hot shock performance. As shown in Example 5, the coating provided by the present invention can also be used for ordinary glass surfaces, and also has good surface properties. As shown in Comparative Example 2, when the molecular weight of the perfluoropolysiloxane oligomer is less than 4000, the corrosion resistance and adhesion performance of the resulting coating are reduced. As shown in Comparative Example 3, when ordinary acrylate is used as a raw material, the hydrophobic and oleophobic properties are reduced, and the anti-fouling ability is poor. It can be seen that the perfluoropolysiloxane coating provided by the present invention has the advantages of good adhesion, strong anti-fouling ability, corrosion resistance and good resistance to cold and hot shock performance, and can be used not only for microcrystalline glass, but also for ordinary glass. The preparation method is simple and suitable for large-scale production.

[0096] like Figure 1 a and Figure 1 As shown in c, the anti-fouling and anti-fingerprint coating provided in Example 1 of the present invention has a consistent initial water drop angle with the perfluoropolyether siloxane coating provided in Comparative Example 1. Figure 1 b and Figure 1 d It can be seen from the comparison that the adhesion of the anti-fouling and anti-fingerprint coating provided by the present invention on the microcrystalline glass is better than that of the commercially available perfluoropolyether siloxane anti-fingerprint coating.

[0097] From the above experimental data and test data, it can be concluded that the anti-fouling and anti-fingerprint coating of a special glass provided by the present invention, when applied to microcrystalline glass, can make the surface of the microcrystalline glass have the characteristics of being hydrophobic, oleophobic, easy to clean, and anti-fingerprint, and has excellent adhesion, anti-scratch and wear resistance, and can protect the glass surface permanently. The preparation and construction methods provided by the present invention are simple, and the raw materials are easily available.

[0098] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing an anti-fouling and anti-fingerprint glass coating, characterized in that: The steps include: According to the mass parts, 40-60 parts of perfluoroalkylethylene and 20-40 parts of fluorine-modified acrylate are mixed and stirred evenly, heated and stirred to 80°C-100°C, reacted at a constant temperature for 8-10h, impurities were removed, and a perfluoroalkyl oligomer with a molecular weight of 4000-8000 was obtained. 10-40 parts of siloxane were added, and the reaction was carried out at 40°C-80°C for 3-4h to obtain perfluoroalkyl siloxane; the perfluoroalkyl siloxane was diluted with a carbon-fluorine solvent to obtain a coating.

2. The preparation method according to claim 1, characterized in that: The carbon chain length of the perfluoroalkyl group in the perfluoroalkylethylene is C4 to C12, and is preferably one or more of 1H, 1H, 2H-perfluoro-1-undecene and heptadecafluoro-1-decene.

3. The preparation method according to claim 1, characterized in that: The fluorine-modified acrylate includes any one or more of perfluoroacrylate, hexafluorobutyl methacrylate, hexafluorobutyl acrylate, trifluoroethyl methacrylate, and heptafluorobutyl acrylate.

4. The preparation method according to claim 1, characterized in that: The impurities are removed by heating to 100°C-120°C and performing rotary distillation to remove the impurities.

5. The preparation method according to claim 1, characterized in that: The siloxane includes any one or more of methoxysiloxane, ethoxysiloxane, hexamethyldisiloxane, decamethyltetrasiloxane and cyclotrisiloxane.

6. The preparation method according to claim 1, characterized in that: The fluorine-containing carbon solvent is a mixture of hexafluoropropylene dimers or trimers.

7. The preparation method according to claim 1, characterized in that: The mass ratio of the perfluoroalkylsiloxane to the fluorine-containing solvent is 0.1-0.5:99.5-99.

9.

8. An anti-fouling and anti-fingerprint glass coating prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Super-hydrophobic oleophobic coating, preparation method thereof and use method

    CN106905816A

  • Anti-fingerprint glass coating with high friction coefficient and preparation method thereof

    CN111410435A

  • Preparation method of perfluoropolyether siloxane compound and anti-fingerprint agent

    CN113583231A

  • Anti-fingerprint touch screen panel

    CN214586840U

  • Novel UV anti-fingerprint coating

    CN215141773U